Wiley not-for-profit GAAP 2020 : interpretation and application of generally accepted accounting principles - Larkin, Richard F. (John Wiley & Sons, Inc., 2020)
Ensure that your not-for-profit accounting is airtight for 2020 Not-for profit organizations have unique characteristics, so they must adhere to a specific set of generally accepted accounting principles (GAAP). Wiley Not-For-Profit GAAP 2020 provides practical guidance on how to identify and apply the relevant standards. This guide is indispensable for professionals responsible for preparing and auditing not-for-profit accounts. You will learn how to interpret the relevant accounting principles and how to apply them, all while minimizing unnecessary effort and eliminating potentially costly errors. This comprehensive yet concise text thoroughly examines the latest standards for measurement, presentation, and disclosure related to not-for-profits. It covers the Financial Accounting Standards Board (FASB) Accounting Standards Codification, all relevant Accounting Standards Updates, and other guidance that applies to not-for-profit organizations, particularly that of the American Institute of Certified Public Accountants (AICPA). With this unrivalled reference tool, your not-for-profit GAAP questions are answered.-Easily understand the latest not-for-profit GAAP with visual aids, including flowcharts, diagrams, and illustrations -Navigate complex requirements and ensure completeness of GAAP disclosures -Stay current with all not-for-profit accounting pronouncements, including FASB, AICPA, and more -Enjoy practical, user-friendly guidance on applying the relevant accounting standards in your not-for-profit organization With Wiley Not-For-Profit GAAP 2020, you can be assured you have the most current, comprehensive accounting information that applies to nonprofit organizations. Stay in compliance and ensure timely, accurate reporting with this authoritative volume.